Rola szkoleń w strategicznej karcie wyników, czyli szkolenia jako narzędzie komunikacji wewnętrznej - Woźniak, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The Balance Scorecard as a tool for communicating strategy within the organization is a development on management by objectives. It is used for the purposes of communication between management and employees, and for making expectations concerning employees' input more comprehensible. The role of trainings in the BSC is defined as a way of providing lacking qualifications. The decision to incorporate trainings into the BŠ cannot however be explained in the "training gap" model - which is project matching economically rational means with goals. The example of attitude-change oriented trainings for employees of a traditional bank serving a retired clientele is used to show that management makes training decisions basing on the issue of internal communications, rather than by rationally assessing chances of success. The text at the same time shows that training theory has to take into account the variety of goals which trainings serve - despite the frequent opinion, that trainings are simply a tool for obtaining new qualifications. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 422-437